2017
DOI: 10.1074/jbc.m116.767954
|View full text |Cite
|
Sign up to set email alerts
|

The Human RecQ4 Helicase Contains a Functional RecQ C-terminal Region (RQC) That Is Essential for Activity

Abstract: Edited by F. Peter GuengerichRecQ helicases are essential in the maintenance of genome stability. Five paralogues (RecQ1, Bloom, Werner, RecQ4, and RecQ5) are found in human cells, with distinct but overlapping roles. Mutations in human RecQ4 give rise to three distinct genetic disorders (Rothmund-Thomson, RAPADILINO, and Baller-Gerold syndromes), characterized by genetic instability, growth deficiency, and predisposition to cancer. Previous studies suggested that RecQ4 was unique because it did not seem to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…It provides information regarding the sizes and shapes of proteins and complexes over a broad range of molecular sizes ranging from several kDa to GDa [32][33][34]. In particular, SAXS can comprehensively characterize dynamic processes in systems where macromolecular structures are evolving under varying experimental conditions (e.g., time, pH, pressure, or different reagents) [35][36][37][38]. In general, a highly purified monodisperse ideal sample without intermolecular interactions is essential for the reconstruction of 3D models from SAXS data.…”
Section: Introductionmentioning
confidence: 99%
“…It provides information regarding the sizes and shapes of proteins and complexes over a broad range of molecular sizes ranging from several kDa to GDa [32][33][34]. In particular, SAXS can comprehensively characterize dynamic processes in systems where macromolecular structures are evolving under varying experimental conditions (e.g., time, pH, pressure, or different reagents) [35][36][37][38]. In general, a highly purified monodisperse ideal sample without intermolecular interactions is essential for the reconstruction of 3D models from SAXS data.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid residues shown to play a role in enzyme function33, were mutated to alanine (shown in Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…During the preparation of this manuscript a study by Mojumdar et al 48. was published, which suggested that RecQ4 features a functional RQC domain that is essential for RecQ4 activity.…”
Section: Discussionmentioning
confidence: 99%